Analysis of Hydrodynamics and Water Quality in Padongko Beach Barru Regency South Sulawesi - Adam, Muhammad -; Ongan, Muh Arden; Paujung, Kristin Ranindaya; Tallulembang, Joyfika Rapuan (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This research aims to analyse the hydrodynamic and water quality in Padongko Beach, Barru regency, South Sulawesi Province. The hydrodynamics and water quality of Padongko Beach effect of community livelihood. The hydrodynamic characteristics of the beach are influenced by the presence of tides, flow, waves and the type of beach. This study used the tidal method, the conjecture ball method, the wave data measurement method, the water quality checker method and the Secchi Disc method to analyses the hydrodynamic and water quality in Padongko beach. Based on the observation and data collecting of tides was taken in the field, the highest tide of 174 cm and the lowest tides of 61 cm. The tide level of Padongko beach was 113 cm, obtaining from reduction of the lowest tide. The tide level of Padongko beach has 113 cm of high, which was qualified as development area of boat harbour of fisherman, auction fish and life resource by benthic organism animal and plants can continue their life well. Implication of sanitation, temperature, turbidity, pH and Dissolve Oxygen (DO) generally in beach has positive low correlation. Therefore, it can conclude that seawater in the beach did not change water quality significantly and recommended for community to do activity in Padongko beach.